Classifying and Coding Design and Construction Information - Nabil Dmaidi (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The search for new approaches to design-construction information integration through the use of computer-based systems is invariably hindered by the need to adopt appropriate representational schemes for the design information by several professions architects, structural engineers, service engineers, quantity surveyors, and by small groups of sub-constructors. Lack of developed coding, classifying and catalogue systems has the greatest impact on the development of integration and the transfer of product information in the light of computer operation. These has been the cause of major problems in the transfer of information between these various bodies (1,14). A proposed design and construction information classifying and coding scheme that facilitates the exchange and manipulation of information in construction projects, while maintaining compatibility with existing classification systems involved in documents like specifications and bills of quantities, will be presented.